2019
DOI: 10.1177/1708538119847898
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of plateletcrit in the prediction of major adverse cardiac and cerebrovascular events in patients with carotid artery stenosis

Abstract: Objectives Platelets play an important role in the pathogenesis of atherosclerosis and the physiopathology of cardiovascular events. Plateletcrit provides complete information on total platelet mass. The relationship between plateletcrit values and long-term outcomes in patients with carotid stenosis is not known. The purpose of the present study is to evaluate the reliability of plateletcrit for predicting major adverse cardiac and cerebrovascular events (MACCE) in patients with carotid stenosis. Methods A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…There was increasing evidence that platelet indices, including MPV and PCT, were found to be significantly associated with vascular risk factors 26 . In the study by Aslan et al 27 , 230 patients with carotid artery disease were included, and high PCT levels were demonstrated to be statistically higher in patients with major adverse cardiac and cerebrovascular events. Furthermore, a study showed that there was a strong relationship between PCT and saphenous vein disease and slow coronary flow 28 .…”
Section: Discussionmentioning
confidence: 99%
“…There was increasing evidence that platelet indices, including MPV and PCT, were found to be significantly associated with vascular risk factors 26 . In the study by Aslan et al 27 , 230 patients with carotid artery disease were included, and high PCT levels were demonstrated to be statistically higher in patients with major adverse cardiac and cerebrovascular events. Furthermore, a study showed that there was a strong relationship between PCT and saphenous vein disease and slow coronary flow 28 .…”
Section: Discussionmentioning
confidence: 99%
“… 33 The results of our study demonstrated that T2DM patients with DPN had significantly higher fibrinogen, lower BMI, and slightly but not significantly decreased MPV and PDW, and BMI was positively associated with MPV and PDW (data not shown), indicating that obese patients have higher MPV and PDW levels than non-obese patients, and weight loss could lead to lower MPV levels, in agreement with previous studies. 38 , 39 Moreover, serum TBA levels were positively associated with MPV and PDW, and negatively with PLT, PCT and fibrinogen, and the subjects in the higher serum TBA quartiles exhibited higher levels of MPV and PDW, and lower PLT and fibrinogen compared with those in the lowest quartile, suggesting that serum TBA might exertathero-protective effects by inhibiting platelet activation and function. Previous studies also revealed that BAs were associated with platelet dysfunction through membrane deformity and inhibited the thrombin response, 40 , 41 and taurocholic acid reduced clot strength via inhibiting platelet activation and aggregation, and promoted tissue plasminogen activator-mediated fibrinolysis.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the paper shows that there are obvious differences in age and hemogram between the population in control group and the population in first cerebral infarction. These biomarkers, including platelets, lymphocytes, neutrophils and monocytes, were good predictors for cerebrovascular events [ 24 ]. In the future, more large-scale research is needed to establish a model based on these indicators to predict cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%